Slow relaxation of photogenerated charge carriers boosts open-circuit voltage of organic solar cells - Upreti, Tanvi; Wilken, Sebastian; Zhang, Huotian; Kemerink, Martijn (The journal of physical chemistry letters, 2021)
Among the parameters determining the eﬃciency of an organic solar cell, the open-circuit voltage (VOC) is the one with most room for improvement. Existing models for the description of VOC assume that photogenerated charge carriers are thermalized. Here, we demonstrate that quasi-equilibrium concepts cannot fully describe VOC of disordered organic devices. For two representative donor:acceptor blends, it is shown that VOC is actually 0.1−0.2 V higher than it would be if the system was in thermodynamic equilibrium. Extensive numerical modeling reveals that the excess energy is mainly due to incomplete relaxation in the disorder-broadened density of states. These ﬁndings indicate that organic solar cells work as nonequilibrium devices, in which part of the photon excess energy is harvested in the form of an enhanced VOC.
Gesehen am 04.12.2021